1974
DOI: 10.1088/0031-8949/10/5/015
|View full text |Cite
|
Sign up to set email alerts
|

Motion in Fluosilicates Studied with Nuclear Magnetic Resonance

Abstract: Motional narrowing of H1 and F19 NMR lines in the fluosilicates of Mn, Fe, Co, Ni, Cu and Zn has been studied. Narrowing due to SiF6 2- complex reorientation occurs at about 225 K, 180 K, 200 K, 150 K, 120 K and 150 K, respectively, and rapid Me(H2O)6 2+ reorientation occurs at 225 K, 220 K, 340 K, 375 K, 350 K and 340 K respectively. This variation is correlated with the variation in density of these nearly isomorphic crystals. At nitrogen temperatures the lattices are stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…At lower temperatures, and for the majority of these compounds (Chevrier & Saint-James, 1990), a structural phase transition is observed. The transition was first reported by Tsujikawa & Couture (1955) at about 223 K with hysteresis of 10 K; it has also been found at 225 K (Skjaeveland & Svare, 1974), around 225 K with a large hysteresis (-30 K) (Jehanno & Varret, 1975) and at 236.2 K (Weir, Halstead & Staveley, 1985). The resulting structure is monoclinic (P21/c) as determined by Syoyama & Osaki (1972) for MgSiF6.6H20.…”
Section: Introductionmentioning
confidence: 60%
“…At lower temperatures, and for the majority of these compounds (Chevrier & Saint-James, 1990), a structural phase transition is observed. The transition was first reported by Tsujikawa & Couture (1955) at about 223 K with hysteresis of 10 K; it has also been found at 225 K (Skjaeveland & Svare, 1974), around 225 K with a large hysteresis (-30 K) (Jehanno & Varret, 1975) and at 236.2 K (Weir, Halstead & Staveley, 1985). The resulting structure is monoclinic (P21/c) as determined by Syoyama & Osaki (1972) for MgSiF6.6H20.…”
Section: Introductionmentioning
confidence: 60%
“…for SiF2-reorientation. The l9 F line narrowing temperature in ZnSiF, * 6 H 2 0 is 150 K from which we derived approximately E, = 5.5 kcal/mole [4] . NiSiF6 -6H20 has the same 19F line narrowing temperature as the Zn salt [4], and we assume that the SiFZ-reorientation in NiSiF6 6H20 as well can be described with eq.…”
Section: Crystal Propertiesmentioning
confidence: 71%
“…Nickel fluorosilicate hexahydrate, NiSiF, -6H20, has been the subject of many physical investigations, including studies of ionic motion with nuclear magnetic resonance (NMR) [1][2][3][4], But we are not aware of any previous dielectric study of this salt. We have found that it has well-defined dielectric losses of Debye type in the temperature range 150-250 K signifying thermally activated motion of some kind of electric dipole moments.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the results obtained from diffraction [2][3][4][5] and NMR [6][7][8] studies shows that the phases found in the various M-FSH differ not only in the elements of symmetry present in the structure, but also in the dynamics of the [M(H 2 O) 6 ] 2+ and [SiF 6 ] 2− ions. The structural disorder observed in the M-FSH series manifests itself in the presence of two possible positions for each type of ion.…”
mentioning
confidence: 99%
“…As the ionic radius of the constituting metal M increases, the reorientation motion of the [M(H 2 O) 6 ] 2+ octahedra stops, creating static disorder [8]. When this happens, the distribution of the metal-water complexes between the positions (C) and (D) is not equal over the crystal.…”
mentioning
confidence: 99%